SOCIAL MEDIA AS A MEDIUM FOR PROMOTION AND DA'WAH OF THE MADHURI PANCAKE DURIAN WOMEN'S BUSINESS UNIT IN BANDA ACEH - Syahril Furqany (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2022)
Social media is currently not only used to share daily activities but is also used as a promotional medium. Promoting products through social media is cheaper and can reach all circles of society. To attract attention, expertise is needed in carrying out designs, product photos, packaging, and having speed in responding to customers. As a Muslim business, of course, you don't only think about profit, but you have to take advantage of this social media as a propaganda medium as well as a promotional media. This study aims to see how the social media accounts of a product are also used as propaganda media as well as promotions and vice versa as promotional media but there is an element of da'wah. The research method was carried out with Participatory Action Research (PAR). By providing briefing on Madhuri Pancake products and assisting the use of social media. The results of the study indicate that a product that is packaged well and then carries out promotions through social media has a positive impact. As a business actor, you are not only concerned with profit. As a Muslim business, they also carry out da'wah by sharing religious information by creating special pillar content as a medium of da'wah. Keywords: Social media, media promotion, and da'wah